Pengembangan Media Pembelajaran Interaktif Berbasis Augmented Reality Berbantuan Assemblr Edu Pada Materi Metamorfosis di Kelas V SD Katolik Santa Theresia Kota Ternate - Desmayanti, Titi; Purnomo, Eko; Abdy, Iwan; Panu, Rasmi Hi (Universitas Khairun, 2024)
This research was conducted to be able to develop a learning media that aims to determine the validity, practicality and effectiveness of AR-based interactive learning media assisted by Assemblr Edu. The model used in this development research is ADDIE which includes 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The data analysis techniques used are media and material expert validation analysis, practicality analysis from the results of student and teacher responses, and effectiveness analysis from the results of pre-test and post-test questions. Based on the results of data analysis, it is concluded that the development of AR-based interactive learning media assisted by Assemblr Edu meets the valid criteria with the average value obtained from the media and material validation results of 93.33%, the results of student and teacher practicality obtained an average value of 77.42%, and the pre-test results obtained a percentage of 14.28% with an average value of 57, while the post-test results obtained a percentage of 100% with an average value of 85. It can be concluded that the AR-based interactive learning media assisted by Assemblr Edu on metamorphosis material in class V of Santa Theresia Catholic Elementary School Ternate City that has been developed is very feasible to use in assisting the learning process.Â